The Responsibility Of Self-Supportive Practicing Midwives In Medical Wastemanagement At Muna District - Sitti nurliyanti Sanwar; Nur Juliana; Endang Sri Mulyawati L (Journal of sciences and health, 2021)
Background: Environment is the unity of space with all objects, power, circumstances, and living things, including humans and behavior. A healthy environment is seen from the protection and good management of the environment. In Muna District there are 12 independent practice midwives who produce medical waste every day. Medical waste must be managed properly. The purpose of this study was to determine the management arrangements for medical practice for independent midwives in Muna District, to analyze the implementation of management of independent midwives' medical waste and to identify the obstacles faced by independent midwives in the management of medical waste. Method: This study is a socialogical juridical study with descriptive research It examines the rules of the law and what happens in reality in society. The juridical aspects used in this study are the laws and implementation regulations related to the responsibility of implementing medical waste management in independent practice midwives Results: The implementation of the management of independent midwife medical practices in Muna Regency has not been carried out properly in accordance with applicable local regulations and policies. Good medical waste management ranging from medical waste selection, storage, transportation, management, burial and hoarding has not been done Conclusions: Socialization needs to be done from the IBI organization and the Muna District Environment Office to provide understanding to independent midwives on medical and procedural waste management in special control and regulation. Keywords: Responsibility, Waste Medical, Independent Practice Midwife